2013
DOI: 10.1002/bse.1828
|View full text |Cite
|
Sign up to set email alerts
|

Being ‘Green and Competitive’: The Impact of Environmental Actions and Collaborations on Firm Performance

Abstract: In this paper, we seek to enhance the understanding of the link between environmental management and firm performance, so contributing to the debate of being "green and competitive". Relying on the resource-based view, we study the effect of different environmental management capabilities on a firm's market and image performance. In particular, we analyze the capabilities to implement product and process-related environmental actions with different types of environmental focus (materials, energy, pollution) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
218
1
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 269 publications
(235 citation statements)
references
References 88 publications
10
218
1
6
Order By: Relevance
“…Dangelico and Pontrandolfo [40] concluded that the benefit of green collaboration includes improving market performance (by accessing new markets and strengthening competitive advantage), enhancing corporate image performance (in its reputation and regulatory compliance), improving manufacturing performance (by increasing its efficiency of materials and energy usage), boosting financial performance (by increasing margins or market share due to customers' willingness to pay a premium price for products) and containing supply chain cost. While the triple objectives-social, environmental, and economic considerations-are integrated, the benchmarking procedure in this study identified environmental standards and social values as the prior objectives for the green component procurement collaboration.…”
Section: Towards the Environmental Standards And Social Valuesmentioning
confidence: 99%
“…Dangelico and Pontrandolfo [40] concluded that the benefit of green collaboration includes improving market performance (by accessing new markets and strengthening competitive advantage), enhancing corporate image performance (in its reputation and regulatory compliance), improving manufacturing performance (by increasing its efficiency of materials and energy usage), boosting financial performance (by increasing margins or market share due to customers' willingness to pay a premium price for products) and containing supply chain cost. While the triple objectives-social, environmental, and economic considerations-are integrated, the benchmarking procedure in this study identified environmental standards and social values as the prior objectives for the green component procurement collaboration.…”
Section: Towards the Environmental Standards And Social Valuesmentioning
confidence: 99%
“…It is not well known how the green benefits can be shared among the members. Green collaboration benefits listed out in the previous studies are reduction of business waste (Azevedo et al, 2011), environmental impact (reducing pollutant emission, using renewable energy sources, avoiding the use of toxic substances, and using environmentally friendly materials), market performance (access to new markets; competitive advantage), corporate image performance (reputation; regulatory compliance), manufacturing performance (efficiency in the use of materials; energy efficiency, innovation), financial performance(Increased margins or market share; customers willingness to pay a premium price for products)and supply chain cost (Dangelico and Pontrandolfo, 2013). The overall benefits out of green collaboration reside with the focal companies and few studies reported the burden to the upstream suppliers.…”
Section: Green Benefitsmentioning
confidence: 99%
“…If we view relationship in terms of dependency and certainties variables, researchers started viewing green relationship from the view of economic, technological and political elements (Vachon, 2007). Similarly, under certainties few researchers attempted to discuss the role of contractual and competence elements (Vachon and Klassen, 2008;Sheu, 2011;Chen and Huang, 2012;Cheng 2011;Gavronski et al, 2011;Dangelico and Pontrandolfo, 2013).Few articles have attempted to discuss the constraints of inter-firm relationship such as bargaining process to move towards green supply chain coordination and the role of interdependence between producer and retailer through third party intervention (Sheu, 2011;2014;Green 2012). …”
Section: Green Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Dangelico and Pontrandolfo, 2013). However, despite a growing interest in finding ways to increase energy efficiency, the industry still harbors untapped energy efficiency potential, conceptualized as energy efficiency and energy service gaps (Hirst and Brown, 1990;Jaffe and Stavins, 1994).…”
Section: Introductionmentioning
confidence: 99%